Intertextualidad rizomática en la obra de Juan Carlos Tolosa (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2020)
In this writing, the use of intertextuality in the work of the composer Juan Carlos Tolosa is analyzed, starting from the premise that the artistic paradigm of the work is reflected in the use of intertextuality. The applied methodology analyzes the object, the form and the intertextual function with the aim of unraveling the concepts and value systems that make up this paradigm. The analysis discovers a rhizomatic intertextuality; a deconstructed subject that relates to the other from alterity; an author who is questioned, and unauthorized; an idea of structure with absence of center; a meaning that is built in play, from its previous condition of absence; a positioning within the history and an incorporation of history within the work; a disbelief regarding metanarratives; and an Other that is seen as a rhizomatic and non-hierarchical set.
Keywords: contemporary Argentine music; artistic paradigm of the 21st century; objects / intertexts; intertextual forms; intertextual functions